Basic Japanese : (Osaka University of Foreign Stidies, 1967)
This book is the second half of the two volumes of basic Japanese-intensive course in speaking and reading containing lessons 20-50. All the text, except in the grammar section, is written in Kana and Kanji, with a space on both sides of the pause group up to lesson 39. After 40, all the sentences are punctuated nearly as is seen in normal Japanese writting.